Neotropical and foreign fruits of special taste and consistency consumed in Colombia (2015)
The present work reviews some Neotropicaland foreign species of fruits that are characterized bytheir special taste, anatomy and consistency. For theColombian territory, the most important commonnames of the species in question are recorded,together with their taxonomic position, plant and fruitmain features, regions where they grow, consumptionmodes, and specific uses.